Thermal effects investigation on electrical properties of silicon solar cells treated by laser irradiation - Ali Pourakbar Saffar; Bahman Deldadeh Barani (International Journal of Renewable Energy Development, 2014)
In this paper, we were investigated electrical properties of monocrystalline and polycrystalline silicon solar cells due to laser irradiation with 650 nm wavelength in two states, proximate irradiation and via optics setup. Thermal effect on the cell surface due to laser irradiation was investigated on electrical properties too. Electrical parameters investigation of solar cells illustrates cell excitement via laser irradiation and efficiency decreases due to cell surface temperature increase. Monocrystalline parameters change with uniform shape due to thermal effect and laser irradiation toward polycrystalline cells.